The new charter of the administrative deconcentrating a lever of the advanced regionalization in Morocco - EL KHALIFI Omar; JALLAL Noureddine; MRHIZOU Hafid (African Scientific Journal, 2023)
The objective of this article is based first of all on a thematic reason, since the new charter of administrative deconcentrating is in the continuity of the great construction site of advanced regionalization that Morocco knows, it is a multiform strategic orientation arousing a particular interest among researchers in the field of political science, governance, among other disciplines. Indeed, the advanced regionalization project constitutes a configuration that is composed of a plethora of parameters, the pillar of which is ineluctably administrative deconcentrating. It is important to analyse it, in view of the importance of the modes of governance of the State. This research addresses various aspects, of a technical, practical, procedural, and economic nature. Our objective is to demonstrate what administrative deconcentrating consists of in Morocco, and what are its illustrations? And this by a study which allows to highlight the convergence between the new charter of administrative deconcentrating, in relation to the various actors.